Meneguhkan Dakwah Melalui New Media - Pardianto., Pardianto. (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2013)
The increasingly crucial role of advanced informa–tion technology, particularly the Internet, in contemporary life has contributed to changes of pattern in proselytizing activities. This article discusses proselytizing activities thro–ugh the Internet media, focusing on three principal issues, the possibility of the Internet to become a medium of pro–selytezing, proselytizing strategies of delivering messages through the Internet, and strategies for strengthening the use of the Internet in proselytizing. Through textual analysis, this article argues that, first, the agencies of proselytizing are supposed to use the Internet as a new media of prose–lytezing. Second, the making use of the Internet as a medium of proselytizing indicates that the proselytizing has given rise to a new pattern in recent development of religious trans–mission.Keywords: internet, pattern of proselytizing, proselytizing media——————————————————————–Artikel ini membahas tentang dakwah melalui me–dia baru (new media) atau internet dengan fokus pada tiga permasalahan, yakni kemungkinan internet menjadi media dakwah, strategi penyampaian pesan dakwah melalui inter–net, dan strategi penguatan pemanfaatan internet dalam berdakwah. Melalui studi teks, artikel ini berpendapat bah–wa, pertama, para pelaku dakwah sudah seharusnya me–manfaatkan media baru beserta aplikasi-aplikasinya sebagai sarana dalam berdakwah. Kedua, dengan menjadikan inter–net sebagai media dakwah, maka sesungguhnya para pelaku dakwah telah meneguhkan pola dakwah baru tersebut.Kata Kunci: internet, pola dakwah, media dakwah.